Limnological status of Trimohini Beel of Rajshahi, Bangladesh - Islam, Md Azizul; Chowdhury, Abdullah Harun (Journal of the Asiatic Society of Bangladesh, Science, 2014)
A total of 38 zooplankton genera and 26 physico-chemical variables were recorded in Trimohini Beel. This beel marked as a medium level of polluted wetland based on the values of the redox characteristics i.e. pH, DO, BOD, COD, Eh and rH2, chlorides, nitrites, ammonium, phosphate values etc. and on the presence of some zooplankton as indicator of pollution. A large number of inland fresh water non-culturable fishes and other aquatic biota of the Trimohini Beel may be eliminated in future due to mixing of continuous chemicals from agriculture fields. It is necessary to conserve the ecosystem of Trimohini Beel for the fresh water non-culturable fishes and other aquatic biota. DOI: http://dx.doi.org/10.3329/jasbs.v39i2.17854 J. Asiat. Soc. Bangladesh, Sci. 39(2): 173-182, December 2013